Investigation of dynamic behavior of geosynthetic reinforced soil retaining structures under earthquake loads - Enünlü, Ali Kasay. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Due to their advantageous engineering properties and cost effectiveness large numbers of Geosynthetic-Reinforced Soil Retaining Walls (GRS-RWs) are being designed and constructed throughout the world and also in our country. In this thesis, in order to gain better insight into dynamic behavior of a GRS-RW under earthquake loads, two 1/2 reduced-scale shaking table tests were carried out using the shaking table facility at the Kandilli Observatory and Earthquake Research Institute (KOERI) of Boğaziçi University. The walls were 1.9 m tall, making them one of the tallest reduced-scale walls of its kind. By installing 8 linear displacement transducers to measure the strains of the geotextile members, 8 laser displacement sensors to measure the displacements of the facing blocks, an LVDT to measure the displacement of the shaking table and 11 accelerometers on several locations of the soil structure and onto the shaking table to evaluate the acceleration amplifications occurred, detailed displacement-time, average strain-time and acceleration-time histories of the components of the GRS-RW were obtained. In addition to the experimental tests, numerical analyses with the finite element (FEM) program Plaxis v 8.4 and the Newmark’s displacement method were utilized. The experimental test results showed that both experimental walls behaved rigidly and almost no residual displacements were observed on the front wall. While Newmark’s analysis confirmed this phenomenon, Plaxis v8.4 simulated the dynamic behavior of the wall reasonably by demonstrating minor residual displacements at the top of the wall attaining to 5 mm and 6 mm for 1st and 2nd experiments, respectively. The general conclusion is that GRS-RWs designed according to the current specifications behave very successfully under earthquake loading conditions.
Keywords: Retaining walls.; Buildings -- Earthquake effects.; Geosynthetics.